Thermal, spectroscopic and x-ray diffraction studies of copper(II) 1,2,4,5-Benzenetetracarboxylates and copper(II) oxalate a study of metal-organic frameworks - Lamprecht, Emmanuel (Rhodes University, Faculty of Science, Department of Chemistry, 2008)
Novel and known metal organic frameworks with copper(II), sodium and 1,2,4,5-benzenetetracarboxylate were prepared by ambient precipitation, solvothermal and gel-synthesis methods, and characterized by single-crystal X-ray diffraction, X-ray powder diffraction, infrared spectroscopy, differential scanning calorimetry, and thermogravimetry with FTIR evolved-gas analysis. Some of these complexes were investigated for guest inclusion properties with water (the original guest species), methanol, ethanol and pyridine. The gel-synthesis products were the most interesting. The novel threedimensional metal-organic framework complex Cu₂ Na(OH)L·7H₂O (where L=1,2,4,5-benzenetetracarboxylate) -formed by gel-synthesis- is a covalent three-dimensional metal organic framework polymer with open channels containing both guest water molecules and water molecules coordinated to sodium. The structure collapsed on dehydration, but was essentially restored to the original structure on rehydration in moist air. On exposure of the dehydrated material to methanol and ethanol vapour, significant uptake of these solvents was observed, and the resolvated structures closely resembled that of the parent material. On heating in dry nitrogen, small amounts of methanol and ethanol remained until about 280 °C, when loss of the remaining guest triggered decomposition of the framework. The related complex, Cu₂¼(OH)½ L·7½H₂O (or possibly Cu₂⅓ (OH)⅔L·8H₂O) -formed by gel-synthesis- had a different physical appearance to Cu₂Na(OH)L·7H₂O above, but had nearly identical X-ray diffraction pattern, mid-infrared spectrum and thermal behaviour. The novel complex Cu₄Na₄L₃·14H₂O -formed by gel-synthesis- is a covalent three-dimensional metal-organic framework with small channels containing both guest water molecules and water coordinated to sodium and copper. Upon dehydration the structure collapsed, but on rehydration in moist air the original structure was partly restored. The dehydrated material did not absorb methanol. Known two-dimensional polymeric complexes [Cu₂L·6H₂O]·4H₂O and [Cu₂L·4H₂O]·2H₂O were also obtained by gel-synthesis, and were characterized and investigated for guest inclusion properties. The structures of these complexes collapsed on dehydration, and were only partly restored on rehydration in saturated water vapour. The dehydrated materials did not absorb methanol. The two-dimensional polymeric mixed-ligand complex Cu₂(pyridine)₄·6H₂O -formed very slowly by gel-synthesis- was characterized by TG-FTIR, and was shown to undergo a complicated decomposition involving the loss of water and pyridine, carbon dioxide and carbon monoxide in various stages. Solvothermal synthesis did not yield materials suitable for single-crystal X-ray diffraction studies or inclusion studies, producing only an anhydrous or hemihydrate complex with the formula Cu₂L·0.65H2O. Ambient precipitation syntheses did not yield materials suitable for singlecrystal diffraction studies, forming products approximately equivalent to the complexes [Cu₂L·6H₂O]·4H₂O and Cu₂¼(OH)½L·7 ½H₂O above. During the course of the above study it was discovered that, on changing the DSC purge from nitrogen to argon, the normally exothermic carboxylate decompositions appeared to become endothermic. The effects of the supposedly inert atmospheres of argon and nitrogen on the decomposition-mechanism of copper(II) oxalate -a well-studied copper carboxylate- were therefore studied by DSC, TG, TG-FTIR and XRPD. DSC experiments were performed in nitrogen and argon at different flow-rates, in various mixtures of nitrogen and argon, and at various heating rates. Regardless of the proportions of nitrogen and argon, the DSC residues consisted mainly of copper metal, a small amount of copper(I) oxide (cuprite) and, in some circumstances, traces of copper(II) oxide (tenorite). Also, regardless of whether TG-FTIR experiments were performed under argon or nitrogen, the gaseous decomposition products consisted mainly of carbon dioxide, with traces of carbon monoxide being detected over part of the decomposition period. Various explanations for the thermal behaviour are discussed, and it is possible that small amounts of O2 or monatomic oxygen were given off during the decomposition under argon. The design and implementation of a low-cost prototype X-ray proportional counter detector system, consisting of a hybrid analog-digital computer built using commonly available electronic components, is presented. This system was designed to replace ageing discrete-transistor designs still in use in earlier X-ray diffractometers. The prototype performs the functions of pulse-shaping, pulseheight discrimination, counting and scaling, and provides both digital and scaled analog outputs.
Keywords: Organometallic compounds; Copper; Oxalates -- Thermal properties; Organic compounds -- Synthesis; Spectrum analysis; X-rays -- Diffraction